PENGGUNAAN APLIKASI QUIZIZZ UNTUK MENINGKATKAN KETERAMPILAN MEMBACA SISWA - Riza BIlharits; Teti Sobari; Aditya Permana (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The background of this research is the low reading interest of students so this has become the focus of research to find alternatives to reading interest that you want to explore in depth and provide solutions to overcome students' low interest in reading. Students' ability in reading comprehension is relatively low, because students tend not to have a deep interest in reading and writing skills, with reading skills being one of the four language skills that are interrelated. This article analyzes media-assisted learning activities to provide information in reading activities so they don't seem monotonous. The purpose of this research is to ascertain whether the use of media-based programs can improve students' comprehension skills in junior high schools. The method used in this study uses descriptive quantitative, to collect data this research performs a proportion which will later be calculated in the results and discussion. Based on these results, it shows that the quizizz application can be used as a supporting media tool to facilitate classroom learning. The use of the quizizz application increases the willingness of students to learn, so that students can learn creatively and actively when learning takes place. Learning to use the quizizz application is proven to be able to improve students' understanding skills when reading so that students can be helped by this application.